Kobiety areny. Status społeczny gladiatorek i toreadorek - Barbarzak, Dawid (Rzym a Półwysep Iberyjski: Różnorodność relacji od starożytności po współczesność, 2019)
The paper tries to compare the social status which was assigned to female-gladiators in ancient Rome and to female-bullfighters (toreras) in modern Spain. The analysis of some written, archeological and plastic sources reveals their presence and social perception over the centuries. In the reports of ancient and modern authors, we can find different opinions about the phenomenon: they range from admiration for fighting skills or female beauty (Martial, Statius, Goya, Daza) to strong criticism (Petronius, Propertius, Juvenal, Sarmiento, Llorens) for mixing gender roles and posing a threat to social, religious or moral order. I also compare some legal regulations which excluded women from active participation in Roman games and Spanish bullfighting.